Keperluan Pendakwah Muslimah dalam Dakwah Kontemporari kepada Masyarakat - Aini Sofia Che Daud; Berhanundin Abdullah (Cyber Media Indonesia, 2020)
Women’s participation and engagement as Islamic preachers nowadays indeed play an imperative role in preaching (messeges da’wah) towards Islam. Their involvement have becoming a main contributor in reaching out to the community about Islam.The study is conducted due to the lack of preachers among women who are directly involve in preaching the society. Besides, this study is also conducted after considering their weaknesses in using contemporary approaches, lack of information and ability to give out opinion in solving current issues pertaining to women. Their roles in delivering the content of da’wah that focus on the aspect of women and society that are based on the Qur’an and Sunnah are undisputable. Therefore, the objective of this study is to investigate the need of Muslim women in delivering contemporary and Islamic teaching about messeges da’wah to the society from the perspective of the Qur’an. This study will employed qualitative method by using documentations supported using verses from the Qur’an, Hadith and views from Islamic scholars about the work at hand. The finding from this study showed that women play significant roles in delivering the messeges da’wah especially in the issues such as in faith, sharia, morals and current women issues based on the verses from the Qur’an. This might be due to the fact that women preachers use a more feminine, personal and empathy approach that might be more effective in delivering Islamic messeges and teaching. DOI: https://doi.org/10.5281/zenodo.3672373